2019
DOI: 10.3390/su11030634
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Approach for the Reduction of Fluoride Ions Mobility in Industrial Waste by Creating Products of Commercial Value

Abstract: In this work, we present the possibility to reduce the amount of fluoride ions in silica gelwaste by using different techniques or to immobilize these ions by creating products ofcommercial value. The leaching of fluoride ions from silica gel waste to the liquid medium wasdone under static and dynamic conditions. It was determined that the removal of fluoride ionsfrom this compound depends on various factors, such as dissociation, solubility, the w/s ratio,reaction temperature, leaching conditions, the adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Silica by-product is material based on amorphous SiO 2 polluted with fluoride compounds. This by-product was obtained from fertilizer plant (Lithuania) and it accumulated about 15,000 tons yearly [14] . Silica by-product is a silica hexaflouride acid neutralization product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silica by-product is material based on amorphous SiO 2 polluted with fluoride compounds. This by-product was obtained from fertilizer plant (Lithuania) and it accumulated about 15,000 tons yearly [14] . Silica by-product is a silica hexaflouride acid neutralization product.…”
Section: Methodsmentioning
confidence: 99%
“…These fluoride compounds retarded the setting process and decreased the mechanical properties of hardened cement pastes or concretes as well. It was suggested thermal treatment [13] or chemical purification method of silica by-product [12] , [14] . All these suggestions are related with the elimination or neutralization of problematic fluoride compounds.…”
Section: Introductionmentioning
confidence: 99%
“…MgCl2•6H2O, FeSO4•7H2O and Ce(SO4)2•4H2O were dissolved for the mixed solution with a molar concentration ratio of Mg:Fe:Ce of 4 To choose the best synthetic method for the adsorbent, two synthesis methods (i.e., the co-precipitation method and hydrothermal synthesis method) were compared. The detailed co-precipitation method was (1) preparing the required experimental solution, (2) adjusting pH with 6 mol•L −1 NaOH to 8.5 and keeping this pH more than 30 min, (3) keeping still for more than 24 h, (4) washing the acquired precipitate and centrifuging all the mixed solution-including precipitate and washing water, (5) drying the precipitate under 65 • C for 24 h, and (6) calcining in the muffle furnace at 600 • C. The detailed hydrothermal synthesis method was (1) preparing the required experimental solution, (2) adding the solution and 6mol•L −1 NaOH to the autoclave and fastening the gap, (3) heating for 6 h under 90 • C, (4) sampling after cooling and exhausting, (5) washing the acquired precipitate and centrifuging all the mixed solution-including precipitate and washing water, (6) washing and drying the precipitate under 65 • C, and (7) calcining in the muffle furnace at 600 • C.…”
Section: Optimization and Preparation Of The Adsorbentmentioning
confidence: 99%
“…Sustainability 2021, 13, 883 2 of 18 Numerous efforts have been devoted to effective F − removal technology development [6][7][8], such as precipitation [9], electrocagulation [10], membranes [11], ion exchange [12][13][14], and adsorption [15][16][17][18]. For example, Shen et al (2003) proposed a treatment measure through the combined electrocoagulation and electroflotation process to remove fluoride ions and found that the anions had a negative effect on fluoride removal efficiency [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation